Children Treated With Pegylated Interferon alfa-2a ± Ribavirin for Chronic Hepatitis C. Issue 1 (January 2016) - Schwarz, Kathleen B.; Molleston, Jean P.; Jonas, Maureen M.; Wen, Jessica; Murray, Karen F.; Rosenthal, Philip; Gonzalez-Peralta, Regino P.; Lobritto, Steven J.; Mogul, Douglas; Pavlovic, Vedran; Warne, Charles; Wat, Cynthia; et al.
ABSTRACT: Objectives: No long-term data have been published on the durability of response following pegylated interferon (PegIFN) treatment in children with chronic hepatitis C. This prospective, multicenter, long-term follow-up (LTFU) study aimed to assess long-term durability of sustained virological response (SVR), long-term safety and tolerability, and the association between IL28B genotype and treatment response, in children previously treated with PegIFN alfa-2a ± ribavirin (RBV) in the PEDS-C trial. Methods: A total of 93 patients were assessed for enrollment, and 38 enrolled in the study. Patients attended 2 study visits: 5 (mean 5.6, range 4.1–6.6) and 6 (6.6, 5.1–7.7) years after treatment cessation. Standardized medical history, physical examination, and laboratory testing were performed at these visits. Reminder telephone calls were conducted at 4 and 8 months after the initial visit. Results: The LTFU cohort was the representative of the original PEDS-C cohort because both baseline and treatment characteristics were comparable. Of the 38 participants, 21 achieved SVR (responders) during the PEDS-C trial and 17 had not (nonresponders). All 21 responders maintained undetectable hepatitis C virus RNA during the LTFU (4.4–7.0 years after achieving SVR) in contrast to the nonresponders who demonstrated persistent viremia. IL28B CC genotype was associated with SVR (67% vs 30% in non-CC, P  = 0.028). Conclusion: Long-term durability of SVR is excellent following PegIFN alfa-2a treatment in children with chronic hepatitis C; SVR is higher in those with IL28B CC versus non-CC.